2014
DOI: 10.4103/0970-2113.142111
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of different dose fractionations schedule of thoracic radiotherapy for pain palliation and health-related quality of life in metastatic NSCLC

Abstract: Introduction:To investigate the effect of different hypo fractionated thoracic radiotherapy schedules in relation to thoracic pain relief, overall survival and post radiotherapy HRQOL in metastatic NSCLC.Material and methods:Stage IV NSCLC and had intra-thoracic symptoms, included in the study. Patients were randomly assigned to three treatments arms. (i) 17 Gy in 2 fractions in one week (ii) 20 Gy in five fractions in one week. (iii) 30 Gy in 10 fractions in two weeks. BPI module was used to assess pain score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Same schedule of thoracic radiotherapy was used by Sau et al for pain palliation and health-related quality of life using FACT-G in non-small cell lung carcinoma patients but improvement in FACT-G score was statistically non-significant. 13 But statistically significant improvement in FACT-G Score in present study shows the promising role of adding gefitinib in the radiotherapy during palliative setting in adenocarcinoma lung patients. Impact of gefitinib concomitant with palliative radiotherapy as well as maintenance therapy with gefitinib in terms of adverse effects observed in the present study found that skin rashes were the most common toxicity, encountered in 59% of the patients.…”
mentioning
confidence: 48%
“…Same schedule of thoracic radiotherapy was used by Sau et al for pain palliation and health-related quality of life using FACT-G in non-small cell lung carcinoma patients but improvement in FACT-G score was statistically non-significant. 13 But statistically significant improvement in FACT-G Score in present study shows the promising role of adding gefitinib in the radiotherapy during palliative setting in adenocarcinoma lung patients. Impact of gefitinib concomitant with palliative radiotherapy as well as maintenance therapy with gefitinib in terms of adverse effects observed in the present study found that skin rashes were the most common toxicity, encountered in 59% of the patients.…”
mentioning
confidence: 48%
“…Among the published trials, 116 trials (52%) used PROs. PROs were primary end points in 45 trials 20,26,28,30,[34][35][36][37]42,48,53,[56][57][58][61][62][63]66,70,74,75,77,79,83,85,93,94,97,103,[108][109][110]113,115,117,118,124,125,127,128,130,133,134,137 (20% of all published trials; 31% of 145 trials clearly stating their primary end point; 39% of 116 trials including a PRO) and secondary end points in 71 trials 24,25,27,29,[31][32][33]…”
Section: Resultsmentioning
confidence: 99%
“…Median (IQR) sample size was 98 (41-230) patients in trials with a PRO as a primary end point, and 50 (31-132) patients in trials with a PRO as a secondary end point. Metastases and thoracic primaries were the most common treated sites (eFigure 3 in the Supplement ), including in 37 published trials 26 , 28 , 30 , 34 , 35 , 36 , 37 , 42 , 48 , 53 , 57 , 61 , 63 , 70 , 74 , 75 , 77 , 79 , 83 , 85 , 93 , 94 , 103 , 108 , 109 , 110 , 113 , 115 , 117 , 118 , 123 , 124 , 125 , 126 , 128 , 133 , 137 (82%) with a PRO as a primary end point and in 50 published trials 27 , 29 , 31 , 32 , 33 , 38 , 39 , 40 , 41 , 43 , 44 , 46 , 51 , 54 , 55 , 65 , 67 , 68 ,…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to Rees et al [11] who also found that 17 Gy in 2 fractions, day 1 and 8 or 22.5 Gy in five daily fractions had no clinically important differences in efficacy between the two regimens. Similarly, Sourav et al [25] randomly assigned patients to three treatments arms: 1) 17 Gy in 2 fractions, day 1 and 8; 2) 20 Gy in five fractions in one week and 3) 30 Gy in 10 fractions in two weeks. Symptomatic relief was equivalent in all the three arms.…”
Section: Symptomatic Assessmentmentioning
confidence: 99%